Pengalaman Mahasiswa Pekerja dalam Pembelajaran Hybrid: Studi Kasus di Sekolah Tinggi Ilmu Ekonomi Balikpapan - Rahimawati, Aisyah Nur; Elya, Efra; Fadilla, Fadilla; anhar, Anhar (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to explore the experiences of working students in undergoing hybrid learning, which is increasingly being implemented in higher education institutions. Working students often face challenges in dividing their time between work and study, which can lead to dual role conflicts. This study uses a qualitative approach with a phenomenological method. Data were collected through semi-structured interviews and documentation, then analysed using thematic analysis to identify relevant patterns of experience. The results show that the main challenges faced by working students include time management, limited access to technology, and schedule conflicts between work and lectures. However, support from the work environment and campus institutions, as well as strategies such as online group learning, help them overcome these obstacles. These findings emphasise the importance of inclusive campus policies, flexible class schedules, and the provision of asynchronous learning materials. In practical terms, this study recommends collaboration between the world of work and higher education to create a learning environment that supports the academic success of working students without disrupting their professional performance.